Experimental Study of Stroke Shortcuts for a Touchscreen Keyboard with Gesture-Redundant Keys Removed - Arif, Ahmed Sabbir; Pahud, Michel; Hinckley, Ken; Buxton, Bill (GI '14 Proceedings of Graphics Interface 2014, 2014)
We present experimental results for two-handed typing on a graphical QWERTY keyboard augmented with linear strokes for Space, Backspace, Shift, and Enter—that is, swipes to the right, left, up, and diagonally down-left, respectively. A first study reveals that users are more likely to adopt these strokes, and type faster, when the keys corresponding to the strokes are removed from the keyboard, as compared to an equivalent stroke-augmented keyboard with the keys intact. A second experiment shows that the keys-removed design yields 16% faster text entry than a standard graphical keyboard for phrases containing mixed case alphanumeric and special symbols, without increasing error rate. Furthermore, the design is easy to learn: users exhibited performance gains almost immediately, and 90% of test users indicated they would want to use it as their primary input method. Demonstration:
Michael A. J. Sweeney Award for Best Student Paper